Criticism and freedom: difficulties and opportunities in the school context - Brito, Leonardo (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The purpose of this article is to analyze the possibilities of criticism and freedom of the subject in the school context. The selected method was the documentary review. The article has been structured in three parts. In the first one, an approach to the idea of pedagogical anthropology is made, with the intention of showing its relevance in educational terms. In the second one, it is highlighted how for two modernity thinkers: Kant and Herbart, freedom is the main pedagogical purpose, for which it is necessary to recognize man as an educable and formable being. It is concluded that freedom, as critical perspective, has difficulties of concretion in the current educational practice; but from the dialogue of the pedagogy with others disciplines it is possible to glimpse opportunities for its deployment.